2019
DOI: 10.1186/s12977-019-0497-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk in an urban African population: a cross-sectional analysis on the role of HIV and antiretroviral treatment

Abstract: BackgroundLife expectancy is increasing in the HIV-positive population and age-related non-communicable diseases, such as cardiovascular disease, (CVD) are seen more frequently. This study investigated to what extent HIV and antiretroviral therapy (ART) is associated with CVD risk in an urban African population.MethodsA cross-sectional study was performed in Johannesburg, South Africa, between July 2016 and November 2017. Both HIV-positive adults (ART-naïve, or on first- or second-line ART), as well as age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This analysis is a sub-analysis of a cross-sectional study that has been described in detail previously ( 16 ). In brief, the cross-sectional study included HIV-positive participants not yet on ART, on first-line and on second-line ART, as well as HIV-negative controls in the inner city of Johannesburg, South Africa, from July 2016 to November 2017.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis is a sub-analysis of a cross-sectional study that has been described in detail previously ( 16 ). In brief, the cross-sectional study included HIV-positive participants not yet on ART, on first-line and on second-line ART, as well as HIV-negative controls in the inner city of Johannesburg, South Africa, from July 2016 to November 2017.…”
Section: Methodsmentioning
confidence: 99%
“…139 Similar results suggesting no difference in cIMT between PLWH taking ART and uninfected comparators, have since been replicated in urban populations in South Africa. 140 On the contrary, a large meta-analysis across sub-Saharan Africa including nearly 9000 individuals from four countries (Burkina Faso, Kenya, Ghana, and South Africa), 99 showed that although traditional CVD risk factors, such as BP, LDL, and age were associated with increased cIMT, HIV serostatus was notably associated with a decreased cIMT (−8.86 μm, 95% confidence interval: −15.7, −2.0). The combined sample appeared strongly representative of older individuals in the region (median age 50 years), with nearly 85% of PLWH on ART.…”
Section: Arteriosclerosis and Pre-clinical Atherosclerosismentioning
confidence: 99%
“…The methods have been described previously. 15 In line with the inclusion criteria of the randomised controlled trials (RCTs) from which the participants were selected, four different groups consisting of PLHIV but not yet or less than 8 weeks on ART (HIV+, ART–), PLHIV and on first-line tenofovir-containing ART regimens for at least 2.5 years (HIV+, ART1), and those on second-line ART for at least 6 months (HIV+, ART2) and HIV-negative controls (HIV–) were identified.…”
Section: Methodsmentioning
confidence: 99%